Capital social, salud mental y bienestar en población migrante: un meta-análisis - Galicia-Hernández, Tania-Evher; Alonso-Arbiol, Itziar; Páez, Darío (Pontificia Universidad Católica del Perú, 2025)
The following meta-analytic review focuses on the relationship between social capital and mental health in the migrant population. Based on 15 studies, with 23 samples and N = 24,000 subjects, a random effect of r = .188 (CI = .121 to .254) was found, explaining 3.5% of variance on wellbeing in comparison to 1% explained by biculturalism as strategy of acculturation. The impact of social capital is greatest on psychological well-being, medium on mental health, and least on subjective well-being. The impact of subjective cognitive measurements is greater than that of structural and mesosocial measures. The effect is greater in men, in older immigrants and in employees. The results confirm that the social capital seems to play a protective role in migrant populations’ mental health and well-being.

A seguinte revisão meta-analítica centra-se na relação entre capital social e saúde mental na população migrante. Com base em 15 estudos, com 23 amostras e N = 24.000 indivíduos, foi encontrado um efeito aleatório de r = 0,188 (IC = 0,121 a 0,254) explicando el 3,5% de la varianza en dem-estar frente al 1% no biculturalismo. O impacto da capital social é maior no bem-estar psicológico, médio na saúde mental e menor no bem-estar subjetivo. O impacto das medidas cognitivas subjetivas é maior do que as medidas estruturais e mesossociais. O efeito é maior nos homens, nos imigrantes mais velhos e nos empregados. Os resultados confirmam que entre as populações migrantes o capital social parece desempenhar um papel protetor na saúde mental e no bem-estar.

La siguiente revisión meta-analítica se centra en la relación entre capital social y salud mental en población migrante. Basados en 15 estudios, con 23 muestras y N = 24,000 individuos, se encontró un efecto aleatorio de r =.188 (IC = .121 a .254) y explica el 3.5% de la varianza en bienestar, frente al 1% de la estrategia de aculturación de biculturalismo. El impacto del capital social es mayor en el bienestar psicológico, medio en la salud mental y menor en el subjetivo. El impacto de las mediciones cognitivas subjetivas es mayor que el de las medidas estructurales y meso sociales. El efecto es mayor en hombres, en inmigrantes de mayor edad y en personas empleadas. Los resultados confirman que el capital social parece desempeñar un papel protector en la salud mental y bienestar de la población migrante.
Social Capital, Mental Health and Wellbeing in the Migrant Population: A Meta-Analysis
Capital Social, Saúde Mental e Bem-estar na Populaçao Migrante: Uma Meta-Análise
Keywords: Psychological well-being; Subjective well-being; Social capital; Immigrants; Meta-analysis; Mental health; Bienestar psicológico; Bienestar subjetivo; Capital social; Inmigrantes; Meta-análisis; Salud mental; Bem-estar psicológico; Bem-estar subjetivo; Capital social; Imigrantes; Meta-nálise; Saúde mental; https://purl.org/pe-repo/ocde/ford#5.01.00